2017
DOI: 10.1007/s00246-017-1761-z
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Routine Coronary CT Angiography in Patients with Transposition of the Great Arteries After an Arterial Switch Operation

Abstract: Coronary complications in patients with transposition of the great arteries (TGA) after an arterial switch operation (ASO) are relatively rare, but of all the possible postoperative adverse events, they are potentially the most dangerous. The fate of the coronary arteries, which are transplanted during the neonatal ASO, remains uncertain. There is also no consensus regarding their postoperative evaluation, especially in asymptomatic patients. The aim of this study was to present the early results of routinely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
0
30
1
1
Order By: Relevance
“…Because of the complex aortic root geometry, its detailed description is frequently difficult in echocardiography, especially in older patients. In our institution, as part of the routine follow-up protocol after an ASO for all patients who are older than 16 years, we perform standard transthoracic echocardiography (TTE), phase-contrast MRI, and coronary computed tomography (CT) angiography [5]. This multimodal approach is used for exact evaluation of the coronary pattern, arterial valve function, root diameters, and flow at different levels.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complex aortic root geometry, its detailed description is frequently difficult in echocardiography, especially in older patients. In our institution, as part of the routine follow-up protocol after an ASO for all patients who are older than 16 years, we perform standard transthoracic echocardiography (TTE), phase-contrast MRI, and coronary computed tomography (CT) angiography [5]. This multimodal approach is used for exact evaluation of the coronary pattern, arterial valve function, root diameters, and flow at different levels.…”
Section: Introductionmentioning
confidence: 99%
“…Ostial fibrosis, intimal thickening, geometrical distortion, and extrinsic compression all undoubtedly occur silently in some patients. 4,5 Indeed, our obligation in addition to stamping out early morbidity from the transfer of aberrant coronaries may also be to remember that the (un)natural history of coronary development post-ASO is largely unknown. Several groups have described a somewhat-intuitive correlation between anomalous coronary branching at the time of ASO and the later development of coronary occlusion by advanced imaging.…”
Section: Commentary: the (Un) Usual Suspectsmentioning
confidence: 99%
“…Large studies from the 1980s and 1990s described a greater mortality for patients with single and intramural coronaries. 4,5 Despite some recent studies still showing a greater mortality in patients with a single coronary, 6 others have concluded that coronary abnormalities are no longer a risk factor for mortality, 7 presumably due to increased surgical experience.…”
Section: Commentary: the Arterial Switch Operation: Is It Still All Amentioning
confidence: 99%
“…Preoperative anatomy is usually determined by echocardiogram, but dual-source cardiovascular CT in neonates has been reported to identify abnormal coronary artery arrangements, which occur in up to one-third of d-TGA patients, with higher sensitivity than echocardiography [64][65][66]. Postoperatively, cardiovascular CT is often used to identify complications such as coronary artery stenosis after reimplantation, which is reported in 8% to 10% of patients who have undergone ASO [67][68][69][70]. CT is also commonly used to assess for main and branch pulmonary artery obstruction after surgical LeCompte maneuver ( Fig.…”
Section: Transposition Of the Great Arteriesmentioning
confidence: 99%
“…CT is also commonly used to assess for main and branch pulmonary artery obstruction after surgical LeCompte maneuver ( Fig. 4) as well as neoaortic root dilation [70]. While CT perfusion imaging may be useful to evaluate for myocardial perfusion defects resulting from coronary artery obstruction, its use has been reported only in conjunction with positron emission tomography (PET) in this population [71].…”
Section: Transposition Of the Great Arteriesmentioning
confidence: 99%